Community Empowerment Through Land Conservation-Based Coffee Production Cooperatives - Munifah, Fadiyah; Tresna, Bahtera Segara (Prospect Publishing, 2024)
The biodiversity protection program of PT Pertamina Patra Niaga AFT Husein Sastranegara focuses on the conservation of the rare Saninten tree in Suntenjaya Village, Lembang Subdistrict, North Bandung Region. This program is carried out in collaboration with Perum Perhutani KPH Bandung Utara and Biope Indonesia. Suntenjaya Village has abundant coffee potential, and the local community utilizes the land around the Saninten conservation area for coffee cultivation. PT Pertamina Patra Niaga AFT Husein Sastranegara recognizes the potential for community involvement in managing the conservation efforts. This initiative is realized through community empowerment by integrating conservation activities with economic empowerment. SEKOP SENI (Sentra Kopi Sejahterakan Petani) program aligns with the existing Saninten Conservation program, which has been ongoing since 2021. The Buana Walatra Sejahtera Cooperative was established as a Coffee Hub for farmers to optimize coffee production, from cultivation to marketing. Both programs emphasize a balance between the economic, social, and environmental pillars, supporting the Sustainable Development Goals (SDGs). SEKOP SENI and Saninten Conservation programs have achieved success in sustainable development aspects, such as increasing the income of beneficiary groups, developing coffee products for inclusive economic growth, improving agricultural productivity through the coffee agroforestry concept, supporting climate action through more environmentally friendly coffee cultivation, and preserving and enhancing biodiversity